Fabry Disease - literature review - Krystian Wdowiak; Agnieszka Maciocha; Julia Wąż; Aleksandra Witas; Adrian Muzyka; Julia Rydzek; Ewa Gardocka (Journal of Education, Health and Sport)
Introduction and objective: Fabry disease (FD) is a rare lysosomal storage disorder that can manifest in classical and atypical forms, with the latter being more common. It results from deficient alpha-galactosidase activity, leading to the accumulation of globotriaosylceramide (Gb3), causing inflammation, cellular damage, and mitochondrial dysfunction. The aim of this publication is to discuss various aspects of Fabry disease based on the latest literature.